The epididymal immune balance: a key to preserving male fertility - Allison Voisin; Fabrice Saez; Joël R Drevet; Rachel Guiton (Asian Journal of Andrology, 2019)
Up to 15% of male infertility has an immunological origin, either due to repetitive infections or to autoimmune responses mainly affecting the epididymis, prostate, and testis. Clinical observations and epidemiological data clearly contradict the idea that the testis confers immune protection to the whole male genital tract. As a consequence, the epididymis, in which posttesticular spermatozoa mature and are stored, has raised some interest in recent years when it comes to its immune mechanisms. Indeed, sperm cells are produced at puberty, long after the establishment of self-tolerance, and they possess unique surface proteins that cannot be recognized as self. These are potential targets of the immune system, with the risk of inducing autoantibodies and consequently male infertility. Epididymal immunity is based on a finely tuned equilibrium between efficient immune responses to pathogens and strong tolerance to sperm cells. These processes rely on incompletely described molecules and cell types. This review compiles recent studies focusing on the immune cell types populating the epididymis, and proposes hypothetical models of the organization of epididymal immunity with a special emphasis on the immune response, while also discussing important aspects of the epididymal immune regulation such as tolerance and tumour control.